Handball offensive analysis: comparative evolution of linear tendency lines between finalist teams in the EHF CL - Vaz, V.; Ferrari, W.; Sarmento, H.; Couceiro, M.; Sousa, T.; Dias, G. (Applied Sciences, 2023)
(1) Background: This study aims to analyze the evolution of the finalist teams in five years of the EHF Champions League and compare winning teams with defeated teams, presenting their evolution along the competition from the quarterfinals to the final; (2) Methods: A total of 35 games were analyzed, corresponding to four games per team over five seasons. Tendency lines were created according to the 13 offensive indicators of winning teams, divided into three macro categories: game actions, goals, and effectiveness of shots; (3) Results: The results indicated 21 linear tendency lines valid for the study. Winning teams presented five increasing lines (ascending line) and 16 decreasing lines (negative slope) during the competition. Assists, goals from the 6 m, and effectiveness at 6 m shots presented an increasing tendency line for winning teams, and the effectiveness of shots, the effectiveness of the organized attack, and the effectiveness of shots from 9-6 m presented a decreasing tendency line; (4) Conclusions: winning teams have more constancy during the competition. Due to the expected increased difficulty in successive matches, tendency lines tend to present decreasing slopes as teams advance toward the final. Nevertheless, winning teams need to adapt to the increasing challenge, describing growth in some key indicators, and being more regular than other teams.